Implementasi Asas Legalitas dalam Pasal 34 Qonun Jinayat - Fathi Yakan A; M Ilham Agustian; Deden Najmudin (Indo Publishing, 2026)
This article examines the implementation of the principle of legal certainty or legality in the Qanun Jinayat, specifically Article 34, a regulation of Islamic criminal law in Aceh. This research is motivated by differing views regarding the application of the Qanun Jinayat, particularly regarding the principle of legality, a fundamental principle in modern criminal law. The principle of legality, which states that